REFLECTIVE SKILLS AS A COMPONENT OF PROFESSIONAL PREPARATION OF STUDENT STUDENT STUDENTS (Pedagogy of Higher and Secondary Education, 2006)
In the article the essential of the specialists training modernization in the conditions of the contemporary university is substantiated. The meaning of the concept “reflective skills ” as an important factor in the student”s training to their further professional activity in defened.